Presence and Correlation of Fusarium graminearum and Deoxynivalenol Accumulation in Silage Corn Plant Parts - Reed, Hannah (Plant disease, 2022)
Corn silage, made from Zea mays, is a high-energy feed that is important for feeding dairy cows. Plant diseases, such as those caused by Fusarium graminearum, can decrease silage corn yields and quality. F. graminearum (teleomorph Gibberella zeae) is an ascomycete fungus that causes Gibberella ear and stalk rot in corn. F. graminearum produces deoxynivalenol (DON), a secondary metabolite toxic to humans and animals. An understanding of the distribution of DON and F. graminearum throughout the corn plant is important for determining the quality of corn silage. A partitioned sample experiment that included two brown midrib silage hybrids and three fungicide treatments was conducted in research plots located in Arlington, WI, U.S.A., in 2018 and 2019. At harvest, stalk and ear parts were physically separated, dried, and ground for analysis. DON concentration (in parts per million) was determined using an enzyme-linked immunosorbent assay, and F. graminearum DNA concentration (in picograms per nanogram) was determined using quantitative PCR. DON and F. graminearum DNA were detected in all samples, demonstrating accumulation of the fungus in stalks and ears of the plant. In 2018, DON contamination was as high as 30 ppm and varied drastically between stalks and ears. In 2019, DON concentrations were much lower (<5 ppm), but were consistently higher in stalk samples than ear samples. Across all samples, DON concentrations and F. graminearum accumulation were highly correlated within the separated stalk (r = 0.78) and ear portions (r = 0.87) but were not correlated between ears and stalks. Depending on the weather and planting conditions in a given year, stalk infections or ear infections may occur by F. graminearum, leading to subsequent DON increases in those respective parts that are independent of each other